Effect of ginger (Zingiber officinale) and garlic (Allium sativum) to enhance health of common carp Cyprinus carpio L .: Sattar Gabber Ajeel and Jamal K. Al-Faragi@ - Al-Faragi, Jamal K. (The Iraqi Journal of Veterinary Medicine, 2013)
The mixing of ginger Zingiber officinale and garlic Allium sativum used at different concentrations ( ginger 10g/kg; garlic 10g/kg; ginger 5g/kg with garlic 5g/kg; ginger 7.5g/kg and garlic 2.5g/kg and ginger 2. 5g/kg and garlic 7.5g/kg in treated 1, 2, 3, 4 and 5 respectively) as a dietary supplements based on their performance in enhancing the fish healthy while control diet was free from ginger and garlic. Haematological parameters of 96 fishes of common carp Cyprinus carpio L. were determined after two months, Red blood cells count (RBCs), white blood cells count (WBCs), hemoglobin concentration (Hb) , and Packed cell volume (PCV) , total plasma protein , albumin and Globulin, liver enzymes (ALT,AST and ALP) using several laboratory techniques and equations. Results showed that all the RBCs , WBCs , PCV , Hb ,parameters and total plasma protein , albumin and Globulin concentrations show increase significantly (P<0.05) in treatment 2 while (AST), (ALT) and (ALP) activities in plasma decreased significantly with increasing levels of garlic and ginger addition.